Ambiguitas Percakapan dalam Wacana Media Sosial Instagram Akun @Totalpolitikcom: Kajian Pragmatik - Ahmad Afian Dwi Utomo; Harun Joko Prayitno (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to identify and analyze the types of ambiguity of meaning and their forms of realization in netizens' comments on the Instagram account @totalpolitikcom, thereby describing the characteristics of ambiguous communication in online spaces. This study uses a descriptive qualitative approach. Data were selected using a purposive sampling technique that focuses on comments containing ambiguity such as satire and sarcasm. Data collection was carried out using the listening and note-taking technique, while data analysis used the distribution method with the Direct Element Sharing (BUL) technique and advanced techniques. The results of the study indicate two types of ambiguity: lexical and grammatical ambiguity. Lexical ambiguity consists of homonymy and polysemy, which appear in the form of evaluative words, metaphorical phrases, informal language, emoticons, and the use of adjectives and generic expressions. Meanwhile, grammatical ambiguity appears in the form of parallel phrases, elliptical structures, unclear contexts, and the formation of non-standard words such as slang and informal word combinations. These findings suggest that ambiguity is a common communication strategy in digital interactions and contributes to the development of pragmatic literacy in cyberspace. The limitation of this study lies in the focus on data that only comes from Instagram comments on @totalpolitikcom, thus it does not yet represent the entire phenomenon of ambiguity on social media. Future research is recommended to expand the object of study to other platforms and to develop digital pragmatic analysis in order to obtain a more comprehensive understanding.